Christianity & new religious movements : an introduction to the world's newest faiths - Cooper, Derek, 1978- (P&R Publishing, 2023)
"In this user-friendly textbook, Cooper explores the world's most dominant new religious movements-such as Jainism, Nation of Islam, Mormonism, and Scientology-from a confessional yet compassionate Christian perspective"--